2018
DOI: 10.1021/acs.molpharmaceut.7b00939
|View full text |Cite
|
Sign up to set email alerts
|

Poloxamer 407/TPGS Mixed Micelles as Promising Carriers for Cyclosporine Ocular Delivery

Abstract: Cyclosporine is an immunosuppressant agent approved for the treatment of dry eye disease and used off-label for other ocular pathologies. Its formulation and ocular bioavailability present a real challenge due to the large molecular weight (1.2 kDa), high lipophilicity, and low water solubility. The aim of the work was to develop an aqueous micellar formulation for an efficient cyclosporine delivery to the ocular tissues, using a water-soluble derivative of vitamin E (TPGS: d-α-tocopheryl polyethylene glycol 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 85 publications
(141 reference statements)
10
78
0
Order By: Relevance
“…The nanomicelles favour solubilisation processes by sequestering the drug in the lipophilic core, formed by the non-polar tails of the surfactant, and interacting with the hydrophilic environment through an outer shell consisting of polar or charged heads. Several reports support the use of surfactant micelles for improved penetration of topically applied drugs through the cornea and enhanced ocular bioavailability [26][27][28][29][30]. Recently (2018), the FDA approved the first commercial product containing 0.09% CyA based on micellization technology (Cequa from Sun Pharmaceutical Ind., Cranbury, NJ, USA) [31].…”
Section: Introductionmentioning
confidence: 99%
“…The nanomicelles favour solubilisation processes by sequestering the drug in the lipophilic core, formed by the non-polar tails of the surfactant, and interacting with the hydrophilic environment through an outer shell consisting of polar or charged heads. Several reports support the use of surfactant micelles for improved penetration of topically applied drugs through the cornea and enhanced ocular bioavailability [26][27][28][29][30]. Recently (2018), the FDA approved the first commercial product containing 0.09% CyA based on micellization technology (Cequa from Sun Pharmaceutical Ind., Cranbury, NJ, USA) [31].…”
Section: Introductionmentioning
confidence: 99%
“…38 In addition, studies are under way to test a different aqueous micellar formulation containing poloxamer 407 and a water-soluble derivative of vitamin E as excipients to enhance CsA solubility and intraocular penetration. 39 These components may provide the advantage of enhanced drug solubility and permeability in addition to beneficial antioxidant effect from vitamin E. 39 On examination, these CsA loaded micelles demonstrated stability upon dilution and increased CsA solubility and delivery to ocular tissues. 39 Another approach to increase bioavailability and residence time of drug is by using contact lenses with hydrogel-loaded drug particles.…”
Section: Formulations Of Cyclosporine a Under Developmentmentioning
confidence: 99%
“…39 These components may provide the advantage of enhanced drug solubility and permeability in addition to beneficial antioxidant effect from vitamin E. 39 On examination, these CsA loaded micelles demonstrated stability upon dilution and increased CsA solubility and delivery to ocular tissues. 39 Another approach to increase bioavailability and residence time of drug is by using contact lenses with hydrogel-loaded drug particles. A recent study has explored monomeric gels loaded with high concentrations of CsA for in situ formation of drug particles, to bypass tolerability issues associated with excipients.…”
Section: Formulations Of Cyclosporine a Under Developmentmentioning
confidence: 99%
“…Since polymeric micelles contain a hydrophobic core and a hydrophilic shell, they are better suited for delivery of hydrophobic drugs across various ocular barriers. Polymeric micelle formulations have been shown to improve bioavailability at anterior eye tissues, offer better intrascleral diffusion and to sustain delivery of therapeutic agents for ophthalmic dug delivery applications (Grimaudo et al, ). A study reported by X. Li et al () demonstrated enhanced corneal permeation (17‐fold higher) and higher bioavailability (twofold higher) of topically administered diclofenac using a methoxy poly(ethylene glycol)–poly(3‐caprolactone) (MPEG–PCL)‐based micelle delivery system when compared to diclofenac solution in rabbit eyes.…”
Section: Ocular Drug Delivery Systemsmentioning
confidence: 99%